The anatomy of account-based marketing - a conceptualisation of strategic dimensions - Mullen, Adam; Marcos Cuevas, Javier; Theoharakis, Vasilis (American Marketing Association, 2022)
Purpose — The purpose of this paper is to conceptualise an emerging B2B strategy known as account-based marketing (ABM). ABM is a mid-to-long-term strategy deployed by enterprise organisations to target, engage, and grow high-potential accounts. Design/Methodology/Approach — A mixture of academic and practitioner literature has been synthesised to create a tentative conceptual model of ABM. Findings — In ABM, digital technologies can be used to scale the engagement process, allowing selling teams to switch from targeting one account to many using pooled intelligence, smart resources, and automation. Originality/Value — This paper presents a conceptual model of ABM, whilst providing a foundation for future research.
Presented at but not included in the Proceedings of the 15th Annual Conference: Global Sales Science Institute, 8-11 June 2022, Frankfurt, Germany
Keywords: Account based marketing; sales and marketing alignment; sales-marketing interface; role of marketing in enabling the sales process; sales automation